Legal and illegal gaming in Malaysia / Nor Asimah Kassim - Kassim, Nor Asimah (Faculty of Law, 1987)
The aim of this paper is an attempt to analyse the distintion between legal and illegal gaming in Malaysia. Gaming per se is not illegal. It is only be illegal by the circumstances in which the game is played. The legality of each game depends on the authorisation of the game. If it is permitted by the government, it is legal. Therfore in determine the legality of each game, the court based it’s decision to the Common Gaming House Act 1953. The Court also imposes sentences on the accussed charged under this act. In preparing this paper, I do not attempt to deal with various types of game but I stress on distinguishing the two category. Therefore I confine my discussion into few category of games. The subject of gaming is a complicated one and intricate points of law often arise. Not only court facing with problems in deciding gaming cases, but the police department are also having great difficulties in handling it. The main problem is lack of evidence and proof in convicting the suspected gamblers…